MODEL DINAMIK TRANSMISIPENYAKIT HEPATITIS B TANPA KEKEBALAN - Atik Rumariyanti; Kartono Kartono; Sutrisno Sutrisno (MATEMATIKA, 2017)
Liver is an important organ for humans. One of the liver disease that received both national and international attention is caused by Hepatitis B. Hepatitis B has the first rank in term of number and spread which it is transmitted through blood or body fluids. In this paper, we discussthe mathematical model in facing Hepatitis B spread.Firstly, we formulate the dynamics of Hepatitis B spread by dividing the population into five classes namely susceptible, exposed, infected, carrier and recovered subpopulation. By using the basic reproduction number value,we analyze the spread of Hepatitis B. From the result, the increasing of the recover rate for infected and carrier subpopulation and the decreasing of infected individu are the best strategy in order to make the rate of Hepatitis B spread is decreasing.